Katalog der mittelalterlichen Handschriften der Zentral- und Hochschulbibliothek Luzern - Kamber, Peter; Mangold, Mikkel (Basel Schwabe Verlag, 2019)
This catalogue describes en detail content, material character, genesis, and history of 115 medieval manuscripts from the fields of theology, liturgy, canon law, church history, history, literature, rhetoric, medicine, and law.
German
Keywords: Bibliographies, catalogues; Medieval manuscripts